Refractive and visual outcome of toric intraocular lens implantation following cataract surgery - Ale, JB; Power, J; Zohs, K; Cunningham, F (Nepalese Journal of Ophthalmology, 2012)
Purpose: To evaluate the refractive and visual outcome of toric IOL implantation for correction of pre-existing corneal astigmatism following cataract surgery. Materials and methods: In this retrospective study, 56 eyes of 30 patients who underwent implantation of toric IOL following regular phacoemulsification were divided into two groups based on the types of toric IOL implanted: group 1 patients received Acrysof toric (Alcon) and group 2 patients received AT-Torbi (Zeiss Meditech) IOLs. Pre-and post-operative corneal and refractive astigmatisms, and post-operative distance vision were investigated. Statistical analysis was carried out using the paired student t-test when necessary. Factors affecting the success of toric IOL implantation are discussed and recommendations are made to optimize the outcome. Results: The mean age of all patients was 75.56 ± 9.87 years. No statistical difference was observed between pre-and post-operative corneal astigmatism (p = 0.819). Postoperative refractive astigmatism was significantly less in both groups (Group 1: p = 0.0014; Group 2: p=<0.00001). The best-corrected distance visual acuity was 6/12 or better in 95 % of group 1 and 100 % of group 2 patients. Conclusion: Toric IOL implantation is a viable and highly predictable method of correcting the corneal astigmatism. It allows correction without compromising the integrity of the cornea. Careful selection of the patient, accurate keratometry and precise alignment of the cylindrical axes are some of the factors to be considered for a superior outcome. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5848 NEPJOPH 2012; 4(1): 37-44